An Indexing System for SNOMED - Wingert, F. (Methods of Information in Medicine, 1986)
A system for automated indexing based on the Systematized Nomenclature of Medicine . (SNOMED) is described. The fundamental algorithms are independent of SNOMED and can also be implemented for other target languages.The algorithms are implemented in a set of programs, the most important problems of which are discussed.
Keywords: SNOMED; Automated Indexing; Nomenclatures